Analysis of stability against rotation of a spherical shell structure subjected to buoyancy. (October 2019) - Zheng, Yanfeng; Luo, Yaozhi; Yang, Chao; Xu, Xian; Wan, Hua-Ping; Zhu, Zhongyi; Heng, Yuekun
Abstract: The main structure of the central detector at the Jiangmen Underground Neutrino Observatory (JUNO) is a spherical shell structure, which has a giant acrylic spherical shell connected to a stainless-steel (SS) reticulated shell with 590 SS rods. The acrylic spherical shell is submerged into water and filled with detection liquid and prone to rotation subjected to considerable buoyancy. The stability against rotation of this super-deep underground spherical shell structure needs to be fully investigated. In this study, an effective and practical method consisting of parametric analysis and optimization procedure is proposed to improve the stability against rotation. Specifically, two indicators, namely, the critical loading multiplier and the rotation angle, are proposed to evaluate the stability against rotation of the acrylic spherical shell in linear and nonlinear stability analyses, respectively. Then, parametric analysis is performed to assess the sensitivity of the stability against rotation to four parameters of interest (i.e., rod outer end constraints, liquid level difference, disc spring stiffness, and rod deviation). Based on the obtained parametric analysis results, the liquid level difference and disc spring stiffness are finally selected as design variables for the subsequent optimization process to further improve the stability against rotation. An efficient scheme combining design variable discretization and exhaustive method is adopted to identify the optimal variable values at which the acrylic spherical shell has good stability against rotation. The results indicate that the proposed method is efficient and effective for optimization of stability against rotation of such super-deep underground spherical shell structure. The proposed method is practical and easy to use for structural designers, and provides an efficient approach to the stability design of such rod-connected spherical shell structures. Highlights: An effective method is proposed to improve the stability against rotation of an underground spherical shell structure. Two indicators are proposed to evaluate the stability against rotation of the spherical shell structure. Influence of the parameters on the stability against rotation is fully investigated to choose the important parameters. An efficient scheme combining design variable discretization and exhaustive method is adopted for optimization.